Estudo do sono, sonol??ncia diurna excessiva, risco de apn??ia do sono e qualidade de vida em pacientes com doen??a renal cr??nica em hemodi??lise - Santos, Israel dos Reis dos (2013)
Introduction: Chronic kidney disease (CKD) is one of the most serious public health problems. The increasing prevalence of CKD in developed and developing countries has led to a global epidemic. Objective: To verify the quality of sleep, excessive daytime sleepiness, risk for obstructive sleep apnea and quality of life in patients with CKD undergone hemodialysis. Methods: Proposes a prospective, consecutive, double-blind, randomized controlled clinical trial. Results: Were involved 214 patients, 59% were male with a mean age of 57 years. The main comorbidities were diabettes Mellitus (45%), hypertension (79%), cardiovascular diseases (5%), HIV (3.2%), hepatitis C virus (2, 8%), cancer (1 9%) and obesity (8.8%). Daytime sleepiness were observed in 107 patients (63%) with a score ??? 10 on the Epworth Sleepiness Scale, while 63 patients had a score ??? 9 points. According to the Berlin questionnaire thirty-three patients had low risk for OSA, while 137 patients (80%) showed high risk. Conclusion: We observed a population characterized by significant daytime sleepiness, high risk for obstructive sleep apnea and the presence of sleep disorders with consequent impairment of quality of life. Considering the close relationship between sleep disorders and CKD, it would be interesting to speculate whether treatment of these disorders could improve the quality of life and reduce mortality. We suggest that further research be conducted to determine longitudinal results regarding the pathophysiology, clinical consequences and effects of treatment with non-invasive ventilation in patients with CKD on hemodialysis.